Effects of Obesity and Diabetes on Sperm Cell Proteomics in Rats - Carvalho, Marcos G. [UNESP]; Silva, Kelry M. [UNESP]; Aristizabal, Viviana H. V. [UNESP]; Ortiz, Pablo E. O. [UNESP]; Paranzini, Cristiane S. [UNESP]; Melchert, Alessandra [UNESP]; Amaro, João L. [UNESP]; Souza, Fabiana F. [UNESP] (My University, 2021)
Infertility caused by male factors is potentially associated with metabolic disorders such as obesity and/or diabetes. This experimental study was conducted in a male rodent model to assess the effects of different diseases on semen quality and sperm proteomics. Ten Wistar rats were used for each treatment. Rats were fed commercial food provided controllably to the control group and the diabetic group, and a hypercaloric diet supplemented with 5% sucrose in water was provided ad libitum to the obese group for 38 weeks. Diabetes was induced with 35 mg/kg streptozotocin. After euthanasia, testicles, spermatozoa, fat, and blood (serum) samples were collected. Spermatozoa were evaluated for quality and subjected to proteomics analyses. Histology and cytology of the testis, and serum leptin, adiponectin, interleukin 8 (IL-8), blood glucose, and testosterone levels, were also assessed. Body weight, retroperitoneal and testicular fat, and the Lee index were also measured. Obesity and diabetes were induced. The diabetic group showed noticeable changes in spermatogenesis and sperm quality. The mass spectrometry proteomics data have been deposited in Mendeley Data (doi: 10.17632/rfp7kfjcsd.5). Fifteen proteins varied in abundance between groups, especially proteins related to energy production and structural function of the spermatozoa, suggesting disturbances in energy production with a subsequent alteration in sperm motility in both groups, but with a compensatory response in the obese group.
Keywords: diabetic; obese; rat; sperm metabolism; sperm protein; spermatogenesis